2017
DOI: 10.1007/s00181-017-1370-y
|View full text |Cite
|
Sign up to set email alerts
|

Actual monetary policy independence in a small open economy: the Polish perspective

Abstract: The aim of this article is to examine the actual degree of monetary policy independence in a small open economy with floating exchange rate that is integrated with the world economy. It is frequently argued that for such a country the primary cost of participation in a currency area is the loss of monetary policy independence. The article raises the question if the proposition of monetary independence provided by floating exchange rate applies to a small open economy, operating within highly liberalised capita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 29 publications
0
1
0
1
Order By: Relevance
“…Similarly, You et al (2014) found evidence that capital control helps to improve a country's monetary independence if the exchange rate is fixed. Goczek and Mycielska (2019) showed that Poland lost its policy independence with a floating exchange rate and highly liberalized capital flows. Goczek and Partyka (2019) also showed that non-Euro members also followed the interest rate of the European Central Bank (ECB), using the 'too small to be independent' argument.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, You et al (2014) found evidence that capital control helps to improve a country's monetary independence if the exchange rate is fixed. Goczek and Mycielska (2019) showed that Poland lost its policy independence with a floating exchange rate and highly liberalized capital flows. Goczek and Partyka (2019) also showed that non-Euro members also followed the interest rate of the European Central Bank (ECB), using the 'too small to be independent' argument.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Jest to dość powszechne założenie wykorzystywane w modelowaniu gospodarki Polski (zob Gottschalk, Moore 2001;. Grabek i inni 2011;Goczek, Mycielska 2019).Uogólniając prawo jednej ceny na przypadek wszystkich dóbr w gospodarce 10 , zakładam, że zachodzi absolutny parytet siły nabywczej pomiędzy krajami (tzw. "silny parytet siły nabywczej", zob.…”
unclassified